Extracorporeal photopheresis for the treatment of acute and chronic graft‐versus‐host disease in adults and children: best practice recommendations from an Italian Society of Hemapheresis and Cell Manipulation (SIdEM) and Italian Group for Bone Marrow Transplantation (GITMO) consensus process. Issue 10 (10th January 2013) - Pierelli, Luca; Perseghin, Paolo; Marchetti, Monia; Messina, Chiara; Perotti, Cesare; Mazzoni, Alessandro; Bacigalupo, Andrea; Locatelli, Franco; Carlier, Paolo; Bosi, Alberto; ,
<x xml:space="preserve">Abstract</x> Background Extracorporeal photopheresis (ECP) is an effective treatment for both acute and chronic graft‐versus‐host disease (GVHD) in children and adults. Despite the large use of this treatment, a large heterogeneity in current application of ECP has been reported so far and recent evidence brought novel issues into some specific topics. Consensus‐based recommendations ameliorate the appropriateness in daily clinical practice and, in turn, optimize the use of health care resources. Study Design and Methods Two Italian scientific societies, the Italian Society of Hemapheresis and Cell Manipulation (SIdEM) and the Italian Group for Bone Marrow Transplantation (GITMO), joined to develop and disseminate recommendations on appropriate application of ECP treatment in patients with GVHD. Accordingly, SIdEM and GITMO named an expert panel that first selected 16 questions that were considered relevant for clinical practice: the questions were subsequently addressed through a revision of the available literature and in consensus meetings. The whole group discussed the proposed recommendations according to the nominal group technique. Results The above‐described approach in turn allowed the panel to agree on 47 practice recommendations. SIdEM and GITMO will disseminate such recommendations to the national transplant centers. Conclusion In conclusion, SIdEM and GITMO have made a scientific effort to provide a useful tool to physicians involved in the field, thus supporting daily clinical practice, as well as strategic decisions in the setting of ECP treatment of GVHD.